THE IMPACT OF DISTORTION ON THE PERFORMANCE OF ADAPTIVE SPATIAL AND POLARIZATION FILTERS - Piza, D. M.; Zalevskiy, O. P.; Bondarev, B. M. (Radio Electronics, Computer Science, Control, 2008)
Efficiency of spatial and polarization filter has been analyzed under effect of power jamming condition. Relationship of factor suppression and power of active jamming have been obtained by simulation and full-scale experiment. Algorithm of expansion radar dymanic range have been proposed, which based on estimation of jamming level and also synhro-control of a signal level of a spatial filter input.